2008
DOI: 10.1002/asia.200700417
|View full text |Cite
|
Sign up to set email alerts
|

α,α‐Diarylprolinol Ethers: New Tools for Functionalization of Carbonyl Compounds

Abstract: Alpha,alpha-diaryl(dialkyl)prolinol ethers constitute a potent organocatalyst family which has been shown to be very general for a broad range of reactions involving enamine and iminium ion activation or a combination of both. The reactions are characterized by an efficient steric control approach and can lead to a variety of alpha-, beta-, gamma-, and alpha,beta-functionalized carbonyl compounds with excellent stereocontrol. As a full expression of their catalytic activity, these compounds are also excellent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
93
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 409 publications
(93 citation statements)
references
References 326 publications
(204 reference statements)
0
93
0
Order By: Relevance
“…The direct chiral amine 5 a [16] and [PdA C H T U N G T R E N N U N G (PPh 3 ) 4 ] co-catalyzed enantioselective a-allylation of aldehyde 1 a with 2 a gave the corresponding alcohol 4 a (after in situ reduction of 3 a) as a single regioisomer with 75:25 e.r. (e.r.…”
Section: Resultsmentioning
confidence: 99%
“…The direct chiral amine 5 a [16] and [PdA C H T U N G T R E N N U N G (PPh 3 ) 4 ] co-catalyzed enantioselective a-allylation of aldehyde 1 a with 2 a gave the corresponding alcohol 4 a (after in situ reduction of 3 a) as a single regioisomer with 75:25 e.r. (e.r.…”
Section: Resultsmentioning
confidence: 99%
“…It was encouraging to find that chiral pyrrolidines 8 and 9 produced more products in 4 h but with no diastereoselectivity (Table 1, entries 4-5). To our delight, the TMS-protected dipenylprolinol 10 [29] catalyzed the enantioselective formation of 2-formyl-aziridine 3 a in 86 % conversion after 3 h with 9:1 d.r. and 99 % ee (entry 6).…”
Section: Resultsmentioning
confidence: 99%
“…In 2005, Jørgensen and co-workers [13], and Hayashi et al [14], independently, discovered that diphenylprolinol silyl ether is an effective organocatalyst [15] [16]. Hayashi et al reported its application for the highly enantioselective, catalytic Michael addition of aldehydes to nitro alkenes.…”
mentioning
confidence: 97%